Improving Speaking Skills through Animated Films Containing Character Values among Students of SD Negeri 112320 Aek Kota Batu - Oom Rohmah Syamsudin; Husnul Khotimah; Khairullah; Muhammad Alfian Tuflih; Juli Yani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
low interest of students in storytelling activities. Many students showed reluctance to participate actively, often engaging in off-topic conversations or joking with peers during class. This behavior reflected a lack of enthusiasm and motivation toward storytelling lessons. The purpose of this research was to improve the storytelling skills of fourth-grade students (Class IV A) through the use of animated films containing character values. The research method used was Classroom Action Research (CAR). The results demonstrated that the use of character-based animated films effectively enhanced students’ storytelling abilities. Improvements were observed in the learning process, including increased student engagement, focus, enthusiasm, and confidence in speaking in front of the class. In terms of outcomes, the average storytelling score improved from 55 in the pre-action stage to 68 in Cycle I, and further increased to 76 in Cycle II, reaching a good category. These findings indicate that both the process and product of students' storytelling skills significantly improved through the use of animated films with character values.